Effect of psychophysical state on different qualification`s handball players on their preparedness - Frolova, L. S.; Glazirin, I. D.; Petrenko, Y. O.; Suprunovich, V. O.; Menshikh, E. E.; Kharchenko, I. A.; Pivnenko, A. O. (Physical Education of Students, 2013)
Studied features a selection of handball players of various skill levels through interdependence parameters psychophysical condition. The study involved 243 handball players of various skill levels. Conducted anthropometric measurements, physical fitness testing, to determine the state of psycho-physiological functions, the calculation of the success of competitive activities. Found that for every subsequent stage of preparing young handball players are selected with certain anthropometric parameters. The selection of qualified athletes indicate a significant advantage of psychophysiological indicators. At the middle level of general physical preparedness depending on the length and circumference of the lower limbs in the making of sportsmanship. Middle and high dependence on the success of competitive activity indicators of spatial perception, logical and spatial thinking is installed in a group of skilled athletes. Identifying additional parameters for the selection of the stages of many years of sports training handball.